Evaluation of New York state's sex offender civil management assessment process recidivism outcomes - Sandler, Jeffrey C. (Criminology & public policy, 2017)
We sought to evaluate New York State's sex offender civil management law by (a) investigating the sexual rearrest of offenders who were screened for possible civil management but who did not receive it and (b) evaluating the accuracy of the multi‐tiered civil management screening and assessment process. Our results indicated that each step in the multi‐tiered assessment process is effectively and accurately identifying higher risk offenders. Additionally, after a 5‐year follow‐up period, 4.6% of the offenders screened by the New York State Office of Mental Health (OMH) who did not receive civil management were rearrested for a sexual offense, which was a significant 36.1% decrease from the 7.2% five‐year sexual rearrest rate found before the enactment of civil management.